2022
DOI: 10.1002/aelm.202200970
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Cadmium‐Free Blue Quantum Dot Light‐Emitting Devices with Stepwise Double Hole‐Transport Layers

Abstract: ZnSe/ZnS core/shell quantum dots (QDs) are environmental‐friendly blue light‐emitting material, which can easily achieve deep blue emission upon external excitation. However, its deep valence band (VB) and numerous defect states remain handicap to realize sufficient performance of quantum dot light‐emitting diodes (QLEDs). In this work, high‐performance cadmium‐free ZnSe/ZnS QLEDs by constructing a double organic hole‐transport layer (HTL) to obtain carrier balance are presented. The double HTLs, which consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition, the study of multi-hole transport layer structures has also become one of the exploration directions. For example, Luo et al [99] prepared a high-performance Cd-free blue ZnSe/ZnS QLEDs by using a TFB/C8-BTBT dual hole transport layer, as shown in Figure 6; its maximum EQE was 7.23%, which is nearly 150% higher than traditional devices based on a single hole transport layer. Research has shown that introducing a TFB/C8-BTBT dual hole transport layer can effectively reduce the charge accumulation between the HTL and QD emission layer, and improve hole injection in Cd-free blue light QLEDs.…”
Section: Hole Transport Layermentioning
confidence: 99%
“…In addition, the study of multi-hole transport layer structures has also become one of the exploration directions. For example, Luo et al [99] prepared a high-performance Cd-free blue ZnSe/ZnS QLEDs by using a TFB/C8-BTBT dual hole transport layer, as shown in Figure 6; its maximum EQE was 7.23%, which is nearly 150% higher than traditional devices based on a single hole transport layer. Research has shown that introducing a TFB/C8-BTBT dual hole transport layer can effectively reduce the charge accumulation between the HTL and QD emission layer, and improve hole injection in Cd-free blue light QLEDs.…”
Section: Hole Transport Layermentioning
confidence: 99%
“…6,7 However, the practical applicability of Cd-based QDs is limited due to environmental concerns. Consequently, recent research has shifted its focus to Cd-free substitutes, including zinc selenide (ZnSe) 12–15 zinc selenide telluride (ZnSeTe), 16–18 indium phosphide (InP), 19,20 and copper indium sulfide (CIS). 21,22 ZnSe-based QDs emerge as promising candidates for Cd-free blue QLEDs due to their narrow full-width at half-maximal values (FWHM) and a broad bandgap of 2.7 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary QLEDs, representing the current state of the art, utilize organic polymeric materials such as poly(4-butylphenyl-diphenylamine) (poly-TPD), ([9,9-dioctylfluoren-2,7-diyl)- co -(4,4′-( N -(4- sec -butylphenyl)diphenylamine))] (TFB), and poly( N -vinyl carbazole) (PVK) in hole transport layers (HTLs), while inorganic zinc oxide (ZnO) or Mg-doped ZnO nanoparticles (NPs) are employed in electron transport layers. 12–15,24 However, the integration of organic HTLs and inorganic electron transport layers introduces substantial energy barriers for charge carrier injection, along with disparities in electron/hole transport mobilities. 15 This combination results in charge accumulation at the interface and interfacial exciton quenching, factors that ultimately diminish operational lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations